PENGARUH KOMITMEN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI (STUDI PADA LAZ HARFA) - Deny Sudrajat; Sana; Syamsurizal (POLITEKNIK LP3I JAKARTA, 2025)
This research aims to analyze employee work productivity at LAZ Harfa. This research uses descriptive quantitative methods to determine the influence of organizational commitment and organizational culture on employee work productivity. This research was caused by inappropriate organizational commitment and organizational culture from employees, resulting in work productivity. The tool used in this research is a Structural Equation Model (SEM) based on Partial Least Square (PLS). PLS is a component or variant-based structural equation model (SEM). PLS model evaluation is carried out by assessing the outer model and inner model, used to test samples (respondents) obtained from the Slovin formula. The test results show that the organizational commitment variable has a t-statistic value of 7.551 > t-table 1.96 and a P-Value value of 0.000 < 0.05. The test results show that the organizational culture variable has a t-statistic value of 12,415 > t-table 1.96 and a P-Value value of 0.000 < 0.05. The test results show that the organizational commitment and organizational culture variables have a t-statistic value of 9,639 > t-table 1.96 and a P-Value value of 0.000 < 0.05.